A arbitragem trabalhista no Brasil - Geraldo, Gisleine Silva (2007)
The purpose of this study is to confirm that Law n. 9.306/96, what interprets the arbitration as adequate multicomposite way to solve the questions involving commercial laws, international business, or the high complexity matters for which the Judiciary is not yet prepared. It also confirms that the mentioned law has no failure concerning the application of its precepts to the labor collective conflicts, by force of the article 114 of the Constitution, what has being accepted as a common sense among labor laws consultants. The same interpretation does not apply to the individual conflicts, as a great diversity of oppinions doesn t reach a common sense about the resignation or negotiation of labor rights the brazilian law establishes that labor rights are not disposable. Nevertheless, this study faces the existing controversy among the so-called the less conservative doctrinaires, who allege the Arbitration Law is totally adequate also for individual labor conflicts, both concerning the solved judicial cases as those still pending on resolution, being considered an alternative way to minimize the present structural and institutional crisis of the brazilian labor judiciary, resulted from many social and economic world transformations the so-called globalization that has deeply affected labor relations, especially those involving labor contracts. It also presents the possibility of an unique brazilian legislation to validate the arbitration in the individual labor conflicts, by comparing the different ways and cultures adequated the arbitration to become a reliable way to solve individual labor controversies, and presenting the historical evolution landscape of the arbitration in the world